Acceptability of six-monthly PrEP dispensing supported with interim HIV self-testing to simplify PrEP delivery in Kenya: findings from qualitative research - Nicholas Thuo; Ashley R. Bardon; Peter Mogere; Catherine Kiptinness; Edinah Casmir; Njeri Wairimu; Emmah Owidi; Phelix Okello; Nelly R. Mugo; Jared M. Baeten; Kenneth Ngure; Katrina F. Ortblad (BMC, 2024)
Abstract Background In Africa, dispensing oral HIV pre-exposure prophylaxis (PrEP) within already strained public health facilities has led to prolonged waiting periods and suboptimal experiences for clients. We sought to explore the acceptability of dispensing PrEP semiannually with interim HIV self-testing (HIVST) versus quarterly PrEP dispensing with clinic-based HIV testing to optimize clinic-delivered PrEP services. Methods We conducted a qualitative study within a non-inferiority individual-level randomized controlled trial testing the effect of six-monthly PrEP dispensing with HIVST compared to the standard-of-care three-monthly PrEP dispensing on PrEP clinical outcomes in Kenya (ClinicalTrials.gov: NCT03593629). Eligible participants were ≥ 18 years, refilling PrEP for the first time, and either in an HIV serodifferent relationship (men and women) or singly enrolled (women only). A subset of participants in the intervention group completed serial in-depth interviews (IDIs) at enrollment, six months, and 12 months. We utilized stratified purposive sampling to ensure representation across participant groups. We analyzed our qualitative data thematically using a combination of inductive and deductive approaches, the latter guided by the Theoretical Framework of Acceptability (TFA). Results Between May 2018 and June 2021, we conducted 120 serial IDIs with 55 participants; 64% (35/55) were in a serodifferent relationship, 64% (35/55) were women, and the median age was 32 years (IQR 27-40). Overall, participants found this novel PrEP delivery model highly acceptable; it was well-liked, private (TFA construct: affective attitude), and less burdensome (TFA construct: burden) compared to standard PrEP delivery. Additionally, participants were confident in their ability to participate in the intervention (TFA construct: self-efficacy). Some participants, however, highlighted model disadvantages, including fewer opportunities for in-person counseling and potentially less accurate HIV testing (TFA construct: opportunity costs). Ultimately, most participants reported that the intervention allowed them to achieve their HIV prevention goals (TFA construct: perceived effectiveness) and that their confidence in at-home HIVST and PrEP continuation increased following each semiannual clinic visit. Conclusions Semiannual PrEP clinic visits supported with six-monthly drug dispensing and interim HIVST was acceptable among PrEP users who experienced the intervention in Kenya. More comprehensive pre-intervention counseling and training on HIVST may help alleviate the client concerns presented, which were often resolved over time with intervention experience.